BIOSORPTION OF HEAVY METALS BY FREE LIVING NITROGEN FIXING BACTERIA (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2022)
Background: The Heavy metals such as chromium, Nickel, cadmium etc. are one of the major contaminants in water pollution. The concentrations of these metals also get biomagnified through food webs and cause serious issues to human health. The contributors of chromium as a pollutant in aquatic system are tannery and leather processing industries. The hexavalent form of chromium is considered as more toxic, mutagenic and carcinogenic form of metal due to its solubility and mobility. The available Physico chemical methods have their own limitations. The use of microbial biomass for treatment of industrial / Waste water is eco-friendly and cost-effective method. The resting cells through a combination of surface reactions with low maintenance energy are the suitable candidate for biosorption. Method: The enrichment, isolation and screening of Cr (VI) tolerant free living diazotrophs was carried out by using Burks Nitrogen Free media. The identification of isolate was done by 16S rRNA gene sequencing. The batch experiment was carried out to study effect of different environmental factors on Cr (VI) biosorption. Results: The potent diazo bacteria isolate showing higher metal tolerance and biosorption on screening was selected and identified as Klebsiella oxytoca. The higher Cr (VI) biosorption of around 83% was seen at pH 4.0, 30⁰ C, with 40 mg/lit. metal and 0.6% whole cells as biomass within 8 hrs. of contact time under static conditions. Conclusion: The obtained isolate can be used as source of bio sorbent for removal of heavy metals from industrial effluents. The further studies are in progress by using isotherm models and for In situ use of bio sorbents.
Keywords: Biosorption; Chromium (VI); Diazobacteria; Heavy metals